The role of the nurses in the prevention of uteros cancer (Research, Society and Development, 2021)
The present work aims to discuss the role of nurses in the prevention of uterus cancer, from preventive examinations, early screening and treatment. Thus, an explanation about the pathology is necessary, as well as its incidence in women today, so that the nurse can be updated in order to promote a dignified treatment for the patient. It is worth emphasizing that the nurse is the key to obtaining a good result in the development of the treatment, emotionally supporting the woman with the pathology, assisting in the relevant exams and offering professional support. The methodology used to present the theme was a bibliographic review, where books, dissertations, scientific articles, theses and magazines were searched, through the academic Google search,Virtual Health Library and SciELO, related to uteros cancer, its causes, pathogenesis, possible treatments and performance of nursing, published from 2008 to 2021, using the deductive method. The study was divided into two chapters, in order to be explained about the importance of nurses in relation to cervical cancer from its prevention, early screening and treatment, through the care needs of affected women and, finally, providing about the link between women's health and disease prevention.